High prevalence of low back pain among young basketball players with lower extremity pain: a cross-sectional study - Yabe, Y.; Hagiwara, Y.; Sekiguchi, T.; Momma, H.; Tsuchiya, M.; Kanazawa, K.; Itaya, N.; Yoshida, S.; Sogi, Y.; Yano, T.; Onoki, T.; Itoi, E.; et al. (BMC Sports Science, Medicine and Rehabilitation, 2020)
Background: Low back pain (LBP) is a common problem among young basketball players in addition to lower extremity injuries. However, studies that focus on LBP with lower extremity pain are limited. From the perspective of the kinematic chain, disrupted lower extremity function can lead to LBP. The association between these two symptoms in basketball players, however, has not been reported. Therefore, this study aimed to clarify the association between lower extremity pain and LBP among young basketball players. Methods: This cross-sectional study was conducted on school-aged basketball players (n = 592). Information regarding their sporting activities was collected using a self-reported questionnaire. Musculoskeletal pain such as low back, knee, and ankle pain was assessed. The sports players with knee and/or ankle pain were defined as having lower extremity pain. Multivariate logistic regression analysis was used to assess the association between lower extremity pain and LBP. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated. The associations of knee or ankle pain with LBP were similarly assessed. Results: School-aged basketball players had a point prevalence of 12.8% for LBP. Compared with the players without lower extremity pain, the players with lower extremity pain had higher rates of LBP, with an adjusted OR (95% CI) of 6.21 (3.57-10.80). There was also a significant association of knee and ankle pain with LBP. Compared with the players without knee or ankle pain, the adjusted ORs (95% CI) for LBP were 4.25 (2.55-7.07) in the players with knee pain and 3.79 (2.26-6.36) in the players with ankle pain. Conclusions: Lower extremity pain was associated with LBP among school-aged basketball players. Further research is needed to clarify the mechanism of this association, which will provide useful information for prevention and treatment of LBP among young basketball players.